Peran Notaris Dalam Pengesahan Perjanjian Pranikah (International Forum of Researchers and Lecturers, 2024)
The role of a notary as a party who has the authority to legalize a marriage agreement in the form of a written agreement, with the intention of converting the marriage agreement into a notarial deed if the parties wish. Recording a prenuptial agreement on a marriage certificate is considered very important because a married couple during the marriage period must have carried out a legal action, if no recording is made, the marriage agreement is only binding for the parties who make it. The method used is a normative legal approach or statutory approach. This paper concludes that: 1) Notaries have an important role in making a marriage agreement deed by writing down the wishes of the husband and wife by applying Article 1338 of the Civil Code concerning freedom of contract and Article 1320 of the Civil Code concerning the valid requirements of the agreement. 2) When viewed from the community's point of view, there are many factors that cause notaries to notarize marriage agreements, such as unclear legal rules such as what and how the law is. It is also difficult for the community to make an agreement between the notary or the dukcapil office and the lack of public interest in making a prenuptial agreement.